Small-scale fisheries management : frameworks and approaches for the developing world - Pomeroy, R. S. (Robert S.); Andrew, Neil (CAB International, 2011)
Small-scale fisheries make up a large proportion of world's fisheries, both by catch and participation. Effective management is essential to ensure access to fish for food and income. Covering social and economic aspects of the fishery management and governance challenge, this book provides guidance on innovative and alternative management measures and methods for small-scale fisheries. The book covers key topics such as rights, policy, co-management, communications and trade, and is an important reference for researchers and students in fisheries science and management as well as fisheries re.